“Brake” and “accelerator”: revisiting tumor cell direct responses and the paradox of aggression in anti-VEGF therapy - Wei, Pei; Li, Jiaqi; Cheng, Xueyan; Lu, Yanxin; Xia, Qiang; Wang, Zhiyong (Frontiers in Immunology, 2026)
Targeted anti-angiogenic therapies against vascular endothelial growth factor (VEGF) are standard treatments for various advanced cancers. However, their clinical benefits are often limited by acquired resistance, with some patients even exhibiting paradoxical tumor aggressiveness and accelerated metastasis. Traditional views primarily attribute this to hypoxia-driven mechanisms within the tumor microenvironment. Based on an analysis of receptor tyrosine kinase (RTK) interactions and pathway rewiring within tumor cells, this paper proposes an integrated “brake-accelerator” model. We posit that in the presence of VEGF, VEGFR2–Mesenchymal-Epithelial Transition factor (MET) heterocomplexes and neuropilin (NRP) co-receptors restrict bypass pathway activity. Upon VEGF blockade, this “brake” is released, and bypass “accelerators” are passively or actively amplified, collectively driving invasive transformation and immune evasion. We identify “direct signal remodeling” in tumor cells as a potentially underappreciated contributor. This process acts as a potential upstream integration node that, alongside treatment-induced hypoxic stress and immune–stromal microenvironment remodeling, constitutes a “tripartite stress” framework. Through Darwinian clonal selection and induced phenotypic plasticity, this framework drives the evolution of tumors towards a more aggressive phenotype. This paper systematically reviews the molecular mechanisms supporting this model, including the regulatory role of VEGFR2-MET complexes, the signal hub function of NRP, and the networked characteristics of escape pathways. Finally, we discuss the implications of this conceptual model for future clinical practice, including the development of dynamic biomarkers based on intrinsic tumor cell characteristics and the design of more precise combination and adaptive treatment strategies to overcome resistance to anti-VEGF therapy and improve patient prognosis.